Model Sekolah PAUD Ramah Anak Berbasis Islam di Kecamatan Singkohor Aceh Singkil - Ratna Rahmawati; Heliati Fajriah; Zikra Hayati (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
Based on the results of initial observations, researchers saw that PAUD Tunas Bangsa Singkohor, researchers saw that teachers lacked preparation in providing learning to children, lacked reinforcement and familiarization with Islamic values in early childhood. The aim is to find out the standards for Islamic-based processes in PAUD Tunas Bangsa Singkohor. This research uses qualitative research methods, with a descriptive approach. Subjects were 3 people and used observation, semi-structured interviews and documentation. The results of this research show that the Islamic-based process standards in PAUD are running properly based on five indicators. (1) PAUD Tunas Bangsa Singkohor uses a scientific approach based on PAIKEMIS by applying questions and answers, observing and informing in accordance with Islamic values, (2) educators teach children to speak politely, but do not accustom children to speak politely, (3) Educators teach children to behave be kind and polite and do not accustom children to behave well and be polite, (4) Educators are lacking in instilling in children a love of local culture, and teaching children to have social life skills and have good morals in socializing, (5) Educators provide a sense of security and comfort but not intense when the learning process is taking place in the classroom.